Primera celebración anual declaratoria del Benemeritazgo. (UNED, 2008)
Aparecen de izquierda a derecha en primer lugar Katya Calderón Herrera, Carlos Manuel Morgan Marín, Luis Guillermo Carpio Malavassi, Maritza Esquivel Chinchilla, Lidia Mayela Hernández Rojas (blusa negra)